White LED based indoor positioning and localization - Kong, Chao (2015)
Accurate, flexible and real-time indoor positioning system will play an important role in future generation of communication networks. The familiar Global Positioning System (GPS) is unfortunately unsuitable in many indoor positioning systems. Hence, ubiquitous indoor positioning system to obtain accurate localization information is required for indoor applications. The rapidly growing trend of using white light emitting diodes (LEDs) for illumination provides an unprecedented opportunity for visible light positioning (VLP) to form the basis for a widely available, economical, and easy-to-use indoor system. This project aims to achieve an accurate indoor positioning under LED lamps environment. The dimensions of the room in the project are assumed to be 5 × 5 × 3 m which represents the length, width and height of the room respectively. Four LED lamps that are modulated with different radio frequencies (RFs) and assumed to be perfectly synchronized are used as transmitters. Photodetectors with wide fields of view are used as receivers. After being photo-detected, the received signals from different LED lamps are filtered by RF filters of different frequencies so that signals from each lamp can be distinguished and separated. The noise distribution within the room size is analysed to simulate the real indoor environment. Among various positioning techniques, phase difference of arrival (PDOA) technique is chosen to measure the distance from each transmitter to receiver. The positioning information can be calculated using these obtained distance data. The positioning error is estimated while adding the Addictive White Gaussian Noise (AWGN) to the received signal according to the noise distribution analysis. Distance error is defined and analysed to evaluate the system performance.